Pemanfaatan Media Digital Interaktif untuk Meningkatkan Pengetahuan Pertolongan Awal Trauma Gigi pada Remaja - Dian Natalina Fuddjiantari; Iin Indah Aris Wati; Ibnu Gunawan; Joko Widyastomo; Novitasari Novitasari (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
Dental trauma is a common issue among adolescents due to high levels of physical activity, yet knowledge regarding initial first aid remains low. Digital media, serving as an engaging educational tool, was utilized to enhance adolescents' knowledge of first aid for dental trauma. This community service activity aimed to improve adolescents' understanding of dental trauma first aid through interactive digital media, specifically videos and Slido quizzes. The implementation involved three stages preparation, execution, and evaluation targeting adolescents aged 15-19 from SMKN 1 Ngasem. During the execution phase, pre-tests and post-tests were conducted covering the definition, types, management, referral, consequences, and prevention of dental trauma. Participant knowledge was evaluated through structured observation regarding their readiness to recognize trauma conditions, determine initial actions, perform management according to first aid principles, and assess the need for referral. The results showed an increase in the participants' average knowledge score from 52.20±10.45 to 79.20±11.30. Improvements were observed across all indicators, demonstrating the potential of digital media to enhance knowledge and prepare adolescents with first aid skills for dental trauma. The activity concluded that the use of interactive digital media is effective in increasing adolescents' knowledge of dental trauma first aid and holds potential as a sustainable tool for oral health education in school settings.